1990
DOI: 10.1093/jn/120.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Control of Rat Liver Fatty Acid Synthase and S14 mRNA Abundance

Abstract: The objective of this research was to evaluate the change in abundance of S14 and fatty acid synthase (FAS) mRNAs under a variety of nutritional conditions to evaluate the hypothesis that the regulation of the S14 gene is similar to that of other proteins involved in lipid metabolism and that changes in S14 expression are comparable to those that occur in FAS expression. Livers from rats fed a high carbohydrate diet were found to contain 350- and 100-fold more S14 and FAS mRNA than livers from rats fasted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…This cytosolic enzyme catalyzes the formation of long chain fatty acids from acetylCoA, malonyl-CoA, and NADPH. Other authors also found that high carbohydrate (60) and cafeteria diets (high fat and high sucrose diet) (59) induced FASN expression at the mRNA level in rats. Patients suffering from non-alcoholic fatty liver disease also show an increase of expression of FASN (61) consistent with the increased FASN expression and fatty liver found in HFD-fed rats.…”
Section: Discussionmentioning
confidence: 85%
“…This cytosolic enzyme catalyzes the formation of long chain fatty acids from acetylCoA, malonyl-CoA, and NADPH. Other authors also found that high carbohydrate (60) and cafeteria diets (high fat and high sucrose diet) (59) induced FASN expression at the mRNA level in rats. Patients suffering from non-alcoholic fatty liver disease also show an increase of expression of FASN (61) consistent with the increased FASN expression and fatty liver found in HFD-fed rats.…”
Section: Discussionmentioning
confidence: 85%
“…FAS, acetyl-CoA carboxylase, and ATP-citrate lyase (24,25)). Nuclear spot 14 protein, the expression of which matches that of lipid synthesis (26), is also induced by premature weaning and disappears in catabolic circumstances such as fasting (27). Hence, leptin, the encoded protein of the ob gene, which is secreted by the adipocyte as part of the sensing program of adipose stores, also behaves as nutritionally regulated (28).…”
Section: Discussionmentioning
confidence: 99%
“…A group of rats was also fasted for 48 h, which both increases fatty acid oxidation and decreases fatty acid biosynthesis [18][19][20]. Table 2 shows the changes seen in plasma glucose and fatty acid levels in the various rat models.…”
Section: Figure 5 Rat Liver MCD Activity and Protein Levels In 6-weekmentioning
confidence: 99%
“…Another well established protocol for altering fatty acid biosynthesis and oxidation in the liver is to starve and then refeed rats [18][19][20]. Table 2 demonstrates the significant decrease in serum glucose and increase in serum fatty acids caused by fasting.…”
Section: Figure 5 Rat Liver MCD Activity and Protein Levels In 6-weekmentioning
confidence: 99%